Impact of experience when using the rapid upper limb assessment to assess postural risk in children using information and communication technologies - Chen, Janice; Falkmer, Torbjorn; Parsons, Richard; Buzzard, J.; Ciccarelli, Marina (Pergamon, 2013)
The Rapid Upper Limb Assessment (RULA) is an observation-based screening tool that has been used to assess postural risks of children in school settings. Studies using eye-tracking technology suggest that visual search strategies are influenced by experience in the task performed. This study investigated if experience in postural risk assessments contributed to differences in outcome scores on the RULA and the visual search strategies utilized. While wearing an eye-tracker, 16 student occupational therapists and 16 experienced occupational therapists used the RULA to assess 11 video scenarios of a child using different mobile information and communication technologies (ICT) in the home environment. No significant differences in RULA outcome scores, and no conclusive differences in visual search strategies between groups were found. RULA can be used as a screening tool for postural risks following a short training session regardless of the assessor's experience in postural risk assessments.